The Effect Achievement Motivation, Leadership Character and Internal Culture Towards Employee's Performance a Case Corporate from Indonesia - Utomo, Joko; Nanere, Marthin; Sutono, Sutono (Universitas Brawijaya, Indonesia, 2017)
The research aims to find out the regression of job achievement motivation towards employee's working satisfaction, the regression of characteristic leadership towards employee's working satisfaction, internal culture towards employee's working satisfaction, job achievement motivation towards employee's working performance, the influence of characteristic leadership towards working performance, the regression of internal culture towards employee's working performance, and the regression of working satisfaction towards employee's working performance in PT. Pura Barutama, the company from Indonesia. The sample is 105 employees. The Questionnaire is used as the instrument while the data analysis is done by using Structural Equation Modeling program. The research found that there is a significant effect of achievement motivation variable towards working satisfaction shown by positive regression. It is also proven by the regression that characteristic leadership is not influential towards working satisfaction of employee; internal culture has a positive effect towards working satisfaction. Meanwhile, achievement motivation has positive regression towards working performance. Characteristic leadership towards working performance is also proven to have regression. Internal culture has a positive effect towards the working performance and working satisfaction also has a positive effect towards working performance.